How Teens with Visual Impairments Take, Edit and Share Photos on Social Media - Bennett, Cynthia; E, Jane; Mott, Martez; Cutrell, Ed; Morris, Meredith Ringel (2018 ACM Conference on Human Factors in Computing Systems (CHI), 2018)
We contribute a qualitative investigation of how teens with visual impairments (VIP) access smartphone photography, from the time they take photos through editing and sharing them on social media. We observed that they largely want to engage with photos visually, similarly to their sighted peers, and have developed strategies around photo capture, editing, sharing, and consumption that attempt to mitigate usability limitations of current photography and social media apps. We demonstrate the need for more work examining how young people with low vision engage with smartphone photography and social media, as they are heavy users of such technologies and have challenges distinct from their totally blind counterparts. We conclude with design considerations to alleviate the usability barriers we uncovered and for making smartphone photography and social media more accessible and relevant for VIPs.